Comparison of In Vitro Stereoselective Metabolism of Bupropion in Human, Monkey, Rat, and Mouse Liver Microsomes - Bhattacharya, Chandrali; Kirby, Danielle; Van Stipdonk, Michael; Stratford, Robert E. (European journal of drug metabolism and pharmacokinetics, 2019)
Background and Objectives Bupropion is an atypical antidepressant and smoking cessation aid associated with wide intersubject variability. This study compared the formation kinetics of three phase I metabolites (hydroxybupropion, threohydrobupropion, and erythrohydrobupropion) in human, marmoset, rat, and mouse liver microsomes. The objective was to establish suitability and limitations  for subsequent use of nonclinical species to model bupropion central nervous system (CNS) disposition in humans. Methods Hepatic microsomal incubations were conducted separately for the R - and S -bupropion enantiomers, and the formation of enantiomer-specific metabolites was determined using LC-MS/MS. Intrinsic formation clearance (CL int ) of metabolites across the four species was determined from the formation rate versus substrate concentration relationship. Results The total clearance of S -bupropion was higher than that of R -bupropion in monkey and human liver microsomes. The contribution of hydroxybupropion to the total racemic bupropion clearance was 38%, 62%, 17%, and 96% in human, monkey, rat, and mouse, respectively.  In the same species order, threohydrobupropion contributed 53%, 23%, 17%, and 3%, and erythrohydrobupropion contributed 9%, 14%, 66%, and 1.3%, respectively, to racemic bupropion clearance. Conclusion The results demonstrate that phase I metabolism in monkeys best approximates that observed in humans, and support the preferred use of this species to investigate possible pharmacokinetic factors that influence the CNS disposition of bupropion and contribute to its high intersubject variability.